A Worldwide Bibliometric and Visualized Analysis in Publications of Research About Hydrogel in Cartilage Repair - Lai, Jieyu; Yu, Dengjie; Ni, Changkai; Zhang, Aohan; Xiao, Wenfeng; Li, Yusheng (Frontiers in Materials, 2022)
Background: Cartilage defect is a common joint disease. Hydrogels are widely used in the area of cartilage tissue engineering because of their ability to repair destroyed cartilage. This study aimed to analyze published research on hydrogels in cartilage repair by using both bibliometric and visualized analyses. Methods: Data was extracted from the Web of Science Core Collection database. Using SPSS, the data were analyzed by bibliometric methodology. In addition, bibliographic coupling analysis, co-citation analysis, co-authorship analysis and co-occurrence analysis were conducted using VOSviewer, and burst detection conducted with CiteSpace helped to indicate the change of keywords. Results: A total of 1245 articles related to hydrogels in cartilage repair from 1997 to 2020 were identified and analyzed. Publication numbers grew steadily and reached 187 papers in 2020. The United States contributed the most to the research with the highest number of times cited, average citations and H-index. Over the studied period, Acta Biomaterialia published the most articles about hydrogels in cartilage repair, numbering 77. Johns Hopkins University was the institution that had the highest average citations per item, and Sichuan University, Harvard University, and Kyoto University were tied for the first by the H-index. Ranking first in the world were the National Institutes of Health, specifically the National Institute of Arthritis Musculoskeletal Skin Diseases, the National Institute of Biomedical Imaging and Engineering and the National Institute of Dental Craniofacial Research, which jointly sponsored 383 articles. Conclusions: This study provided analyzed data for global researchers to better understand the facts and future development of research on hydrogels in cartilage repair. The number of publications on hydrogels in cartilage repair will probably still increase in the next years according to the current trend. Moreover, tissue engineering is a promising way to cure cartilage damage in the future. In addition, mesenchymal stem cells and hydrogels are ideal seed cells and brackets in tissue engineering, respectively.